The metaphysical meaning of extension in Newton - Bião, Ruslane (Sofia, 2024)
To clarify the concept of extension, Newton first formulated, in De gravitatione, a criticism directed at Cartesian metaphysics by identifying the problem of the identity between body and extension that Descartes had previously established in his concept of movement. In this case, the analysis of the Cartesian concept of extension, in the way Newton rethought it, led to a reflection on the complex relationship between Metaphysics and Natural Philosophy when substance is confused with extension, space with place, in an attempt to explain the movement of bodies. To this end, the foundation of the concept of movement will need to be established within the connection between cause and effect based on its natural manifestations and from which Newton will seek to formulate the concept of active principle in Natural Philosophy.